Research of the Process of Ozonation and Sorption Filtration of Natural and Anthropogenicly Pollated Waters - ABDYKADYROVk, Askar; MARXULYk, Sunggat; BAIKENZHEYEVA, Aigul; BAKYT, Gabit; ABDULLAYEV, Seidulla; KUTTYBAYEVA, Ainur Ermekkalievna (Journal of Environmental Management and Tourism; Vol 14 No 3 (2023): JEMT, Volume XIV, Issue 3(67), Summer 2023DO - 10.14505/jemt.v14.3(67).20, 2023)
This scientific research work is written based on the problem of studying the process of ozonation and sorption filtration of natural and anthropogenically polluted waters. Scientific research work of our country is diverse It was prepared in the laboratory of water ozonation, and purification technology and equipment of Kazakh National Research Technical University named after K. I. Satbayev based on long-term research conducted in cities and regions. The current state of ozonation equipment and active carbon production is considered in the research work. The scientific research work is intended to solve problems and tasks related to the use of ozonation and sorption water purification methods for employees of the sector of quality water supply and water treatment. In addition, the research work is devoted to the problems of water purification using ozone. Provides general information about the properties of ozone, its interaction with inorganic and organic compounds. The main methods of obtaining ozone, the effect of design parameters on the efficiency of ozonators are shown. The main domestic and foreign manufacturers of ozonation equipment are presented. In the research paper, considering the effectiveness of removing various organic and inorganic pollutants of natural and anthropogenic origin, microbiological pollutants, the authors' long-term research on purification and disinfection of natural waters are systematized. Production experience of using ozone in foreign and Kazakh water facilities, as well as in local water treatment plants is presented.